2013
DOI: 10.1177/1753193413489046
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between sonographic and electrophysiological parameters in carpal tunnel syndrome

Abstract: A prospective study was carried out to investigate any correlation between electrophysiological and sonographic findings in patients with a clinical diagnosis of carpal tunnel syndrome. A total of 113 patients (113 wrists) in 90 women and 23 men, with a mean age of 60 years, underwent sonographic and electrophysiological examination. Fifty-five patients (48%) had mild, 43 (38%) moderate and 12 (11%) had severe conduction disturbances and three patients had normal conduction. Sonographic measurements showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
18
0
4
Order By: Relevance
“…They noted a wide variation in cutoff values used to define a positive ultrasound or EDx result. Similar to other investigators, these authors concluded that the wide variations in diagnostic value reported in the literature have prevented effective application of PN-USI in the diagnosis of CTS [4,29]. In addition, there is inconsistent data in the literature with respect to using PN-USI to differentiate among mild, moderate, and severe FMMW based on EDx findings.…”
Section: Ultrasonography In Carpal Tunnel Syndromesupporting
confidence: 68%
“…They noted a wide variation in cutoff values used to define a positive ultrasound or EDx result. Similar to other investigators, these authors concluded that the wide variations in diagnostic value reported in the literature have prevented effective application of PN-USI in the diagnosis of CTS [4,29]. In addition, there is inconsistent data in the literature with respect to using PN-USI to differentiate among mild, moderate, and severe FMMW based on EDx findings.…”
Section: Ultrasonography In Carpal Tunnel Syndromesupporting
confidence: 68%
“…Results have been mixed, but in general both tests seem comparable in sensitivity and specificity, with some tendency for greater accuracy with NCS . A positive correlation between the severity of HRUS changes and EDx grade has been established by some investigators, but not by others . HRUS may remain normal even in patients with severe CTS .…”
mentioning
confidence: 95%
“…10 A positive correlation between the severity of HRUS changes and EDx grade has been established by some investigators, 8,14 but not by others. 15,16 HRUS may remain normal even in patients with severe CTS. 17 On the other hand, clinically definite CTS cases with normal NCS are well described, and their proportion may reach 25%.…”
mentioning
confidence: 97%
“…In addition to determining the diagnostic value of ultrasonographic measurements in radial neuropathy at the SG, we performed a correlation analysis of CSAs and electrophysiological severity scale scores and found no significant correlation. Although not related to radial neuropathy, the relationship between ultrasonographic measurements and electrodiagnostic studies has been reported in several previous studies [ 16 , 29 , 31 - 33 ], but there have been conflicting results. This could be explained by several factors such as variability in nerve pathologies related to causes, relationship(s) with peripheral tissue, and the concept that ultrasound primarily assesses anatomy and electrodiagnostic studies primarily assess nerve function [ 16 ].…”
Section: Discussionmentioning
confidence: 94%